2017
DOI: 10.1016/j.nlm.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle myosin II inhibition disrupts methamphetamine-associated memory in females and adolescents

Abstract: Memories associated with drug use can trigger strong motivation for the drug, which increases relapse vulnerability in substance use disorder (SUD). Currently there are no treatments for relapse to abuse of psychostimulants, such as methamphetamine (METH). We previously reported that storage of memories associated with METH, but not those for fear or food reward, and the concomitant spine density increase are disrupted in a retrieval-independent manner by depolymerizing actin in the basolateral amygdala comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Mice were euthanized by cervical dislocation under anesthesia, and the blood and lungs were collected 1, 3, 5, and 7 d after LPS application. LatA (0.5 mg/kg) (14), BLEB (5 mg/kg) (15), Y27632 (5 mg/kg) (16), ML-7 (2 mg/kg) (17), and Tb4 protein (10 mg/kg) (18) were intraperitoneally injected twice daily after LPS administration. CD11b neutralizing antibody (100 mg) (19) was reconstituted in sterile PBS and injected through the tail vein once daily after LPS treatment.…”
Section: In Vivo Lps Drug Cd11b Antibody and Tb4 Protein Administrmentioning
confidence: 99%
“…Mice were euthanized by cervical dislocation under anesthesia, and the blood and lungs were collected 1, 3, 5, and 7 d after LPS application. LatA (0.5 mg/kg) (14), BLEB (5 mg/kg) (15), Y27632 (5 mg/kg) (16), ML-7 (2 mg/kg) (17), and Tb4 protein (10 mg/kg) (18) were intraperitoneally injected twice daily after LPS administration. CD11b neutralizing antibody (100 mg) (19) was reconstituted in sterile PBS and injected through the tail vein once daily after LPS treatment.…”
Section: In Vivo Lps Drug Cd11b Antibody and Tb4 Protein Administrmentioning
confidence: 99%
“…NMII inhibition disrupts METH-associated memory and reverses BLA spine density with equal efficacy to direct actin depolymerization via Latrunculin A (19,(29)(30)(31). If the persistent BLA spine motility changes observed here are connected to the memory disruption, we would predict that the motility is NMII-dependent.…”
Section: Discussionmentioning
confidence: 78%
“…We next assessed BLA spine motility following METH-associated learning as a measure of spine actin dynamics. We have previously demonstrated that METH-associated memory is vulnerable to disruption by Blebb days after training in adult and adolescent (P28-35) male and female mice (30). In the current study, P28-35 male and female Thy1-GFP(m) mice underwent conditioned place preference (CPP) training with either saline or METH, followed by imaging one to three days later ( Fig.…”
Section: Meth Conditioning Increases Basal Spine Motility In Bla Butmentioning
confidence: 69%
See 2 more Smart Citations